The cis‐regulatory code of Hox function in Drosophila - Sorge, Sebastian; Ha, Nati; Polychronidou, Maria; Friedrich, Jana; Kaspar, Petra; Mundorf, Juliane; Rätzer, Jenny; Papagiannouli, Fani; Lohmann, Ingrid (The EMBO journal, 2012)
Precise gene expression is a fundamental aspect of organismal function and depends on the combinatorial interplay of transcription factors (TFs) with cis‐regulatory DNA elements. While much is known about TF function in general, our understanding of their cell type‐specific activities is still poor. To address how widely expressed transcriptional regulators modulate downstream gene activity with high cellular specificity, we have identified binding regions for the Hox TF Deformed (Dfd) in the Drosophila genome. Our analysis of architectural features within Hox cis‐regulatory response elements (HREs) shows that HRE structure is essential for cell type‐specific gene expression. We also find that Dfd and Ultrabithorax (Ubx), another Hox TF specifying different morphological traits, interact with non‐overlapping regions in vivo, despite their similar DNA binding preferences. While Dfd and Ubx HREs exhibit comparable design principles, their motif compositions and motif‐pair associations are distinct, explaining the highly selective interaction of these Hox proteins with the regulatory environment. Thus, our results uncover the regulatory code imprinted in Hox enhancers and elucidate the mechanisms underlying functional specificity of TFs in vivo.